(untitled) (Alternautas, 2016)
Throughout this last decade and a half, and in parallel to the general crisis of global capitalism, a wide popular urban sector of the periphery (from Argentina but also from elsewhere) sought a favorable cycle that included themselves in consumption. One could think of this new access to wealth as a process of liberation (unlike the orthodox critique that interprets it as alienation), with the caveat of amplifying the very notion of “liberation”. With the increase of consumption there are new modes of sensing, desiring, thinking, socializing; but also other ways of being, loving, enjoying, and dying that have been radically altered. New possibilities emerge and the traditional knowledge of governing populations radically breaks down. Far from pointing to a decline in the old forms of social organization, collective action opens a new gap in a time that is unprecedented and incalculable.